Sub-1 ns characterization methodology for transistor electrical parameter extraction. (June 2018) - Qu, Yiming; Chen, Bing; Liu, Wei; Han, Jinghui; Lu, Jiwu; Zhao, Yi
Abstract: In this paper, a novel method is proposed for the extraction of the transistor electrical parameters at the nanosecond timescale. This technique is enabled by an ultra-fast measurement (UFM) system that mainly contains the arbitrary waveform generator and a high-speed real-time oscilloscope. De-noising, synchronization and calibration problems are solved to improve the accuracy and precision. To circumvent the circuit problem at the drain of the transistors, a three-dimensional (3-D) I-V characterization solution is reported, and the I D - V G and I D - V D measured at sub-1 ns time are then drawn. The I-V curves measured in 800 ps show unprecedented agreement with that measured by a standard parameter analyzer and can be used for device/circuit modeling and reliability behaviors studies. Highlights: This paper proposed a novel method for accurate extraction of transistor electrical parameters at the nanosecond timescale. This technique is enabled by an ultra-fast measurement system, mainly including a waveform generator and a oscilloscope. De-noising, synchronization and calibration problems are solved to improve the accuracy and precision. By 3-D I-V characterization solution, I D - V G and I D - V D measured at sub-1 ns time are obtained on bulk Si and SOI MOSFETs. This sub-1 ns methodology can be used for device/circuit modeling and reliability behaviors studies.